Knowledge of antimicrobial resistance among medical interns in a tertiary care teaching hospital at Karnataka: institution based cross sectional study - Subramani, Nandhagopal; Nagaveni, S. J. (International Journal Of Community Medicine And Public Health, 2025)
Background: Antimicrobial resistance is an escalating global health issue, predominantly fueled by the excessive use and improper application of antimicrobials. Medical interns, as future healthcare providers, play a crucial role in tackling this issue through careful prescribing and patient education. Methods: A cross-sectional, questionnaire-based study was conducted among medical interns. A structured and validated questionnaire was used to assess their knowledge, regarding antimicrobial resistance. Data were analyzed using descriptive statistics. Results: A total of 133 participants in the study, in that 71 are males and 62 are females, with a mean age of 23.6 for both groups. findings revealed that (n=119 89.4%) of interns recognized antimicrobial resistance as a significant public health issue. However, only (n=59 44.3%) were aware of antimicrobial stewardship programs. Additionally, (n=93 73.6%) acknowledged the importance of hand hygiene in preventing antimicrobial resistance. Overuse of antimicrobials in hospitals (n=78 58.4%) and incorrect dosing (n=70 52.6%) were the most commonly perceived causes of antimicrobial resistance. Regarding solutions, (n=40 30%) of participants believed completing the full course of antimicrobials was essential, and (n=36 27%) emphasized avoiding self-medication as a crucial step in controlling antimicrobial resistance. Conclusions: Participants demonstrated a strong understanding of antimicrobial resistance as a significant public health concern, gaps were identified in areas such as antimicrobial stewardship awareness and misconceptions about antibiotic discontinuation. Strengthening antimicrobial stewardship programs and promoting rational prescribing practices will be key in addressing antimicrobial resistance effectively.